Multiple-symmetry-protected lantern-like nodal walls in lithium-rich compound LiRuO2 - Gao, Hongli; Meng, Weizhen; Wang, Lirong; Deng, Jinxiang (Frontiers in Physics, 2022)
Topological semimetals have attracted wide attention due to their potential applications, such as electronic devices, electrocatalysis etc. Herein, based on first-principles calculations and symmetry analysis, we first report that ternary compound pnnm-type LiRuO2 is a typical lantern-like nodal wall semimetal. Specifically, without considering spin-orbit coupling (SOC), one-dimensional (1D) two-fold degenerate bands on the ki = ±π (i =x, y) planes form two-dimensional (2D) topological state (namely nodal surface) under the constraint of multiple symmetry operations. Besides, the symmetry-enforced nodal network is formed on the kz = ±π planes. Finally, these nodal networks and nodal surfaces are coupled together to form lantern-like nodal walls. Remarkably, these topological states are protected by multiple symmetries, namely nonsymmorphic two-fold screw-rotational symmetry [S2i (i = x, y)], time-reversal symmetry (T), inversion symmetry (I), glide plane symmetry (σz), two-fold rotational symmetry (C2x/y). Besides, we further discuss the effect of spin-orbit coupling on the lantern-like nodal walls. We find that even if LiRuO2 contains S2z and T symmetries, these nodal surfaces and nodal networks are still broken. Then, due to the existence of I and T symmetries, Dirac nodal lines and Dirac points are formed in the low energy region. Therefore, our work indicate that the LiRuO2 is an excellent material platform for researching multiple topological states.